The quality of working life: gap between perception and idealization impact of gender and status - Salès-Wuillemin, Edith; Minondo-Kaghad, Brigitte; Chappé, Julien; Gélin, Morgan; Dolard, Adrien (Frontiers in Psychology, 2023)
Background Many studies show the existence of gender inequalities at work. For example, in France, only 37% of women have a managerial role, which is far from parity. Among these gender inequalities, the present study considers the Quality of Working Life (QWL) for women and managers. Method This study measures the Quality of Working Life (QWL) perceived by individuals according to their gender (Women vs. Men) and their status (Managers vs. Co-workers). A questionnaire was distributed to 1,321 employees. It comprised two scales: the WRQoL scale and the QUALTRA-Scale. The QUALTRA-Scale permits the calculation of an index δ that measures the gap between the ideal QWL and the perceived QWL. Results The ANOVA (2×2) revealed an impact of status on the perceived QWL on both scales. There was no gender effect. However, there was an effect of both gender and status on the index δ of the QUALTRA-Scale. In particular, for the Women group, δ was higher for the Social Relationships at Work whereas for the Co-workers, it was higher for the Work Environment. Conclusion These results are discussed, highlighting the value of measuring the ideal QWL as a reference point for assessing the QWL.